Corporeal generosity: Breastfeeding bodies and female‐dominated workplaces. Issue 3 (22nd February 2022) - Burns, Elaine; Gannon, Susanne; Pierce, Heather; Hugman, Sky
Abstract: While gender equality at work and the gendered parameters of workplace conditions are of interest to feminist researchers, this paper brings together sociological and public health perspectives to interrogate factors impacting women who return to work (RTW) while maintaining breastfeeding. Our inquiry is focused on female‐dominated professions, teaching, nursing, and midwifery, and our findings suggest that breastfeeding obstacles exist even when gender‐inclusive policies appear to support women. Workplaces generate both overt and subtle barriers to breastfeeding, which force many women to stop earlier than they intended or create ongoing worry about maintaining breastmilk supply. Interviews with participants who maintained breastfeeding after RTW generated three overarching themes: women's determination to get back into the workforce, not wanting to "rock the boat", and the difficulty in keeping their "head above water". Despite workplace policies that appeared to support breastfeeding, the workplace catered to a supposedly gender‐neutral worker and policies did not translate into practice. Given the many sacrifices that women make to maintain breastfeeding, the level of workplace apathy was surprising, especially in female dominated professions. Our research foregrounds breastfeeding corporeality, not as excess but as an inevitable and essential feature of workplaces, which needs to be acknowledged and accommodated.